Influence of context-sensitive rules on the formation of orthographic representations in Spanish dyslexic children - Suárez-Coalla, Paz; Avdyli, Rrezarta; Cuetos, Fernando (Frontiers in Psychology, 2014)
Spanish-speaking developmental dyslexics are mainly characterized by poor reading fluency. One reason for this lack of fluency could be a difficulty in creating and accessing lexical representations, because, as the self-teaching theory suggest, it is necessary to develop orthographic representations to use direct reading (Share, 1995). It is possible that this difficulty to acquire orthographic representations can be specifically related to words that contain context sensitive graphemes, since it has been demonstrated that reading is affected by this kind of graphemes (Barca, et al., 2007). In order to test this possibility we compared a group of dyslexic children with a group of normal readers (9 - 13 years), in a task of repeated reading. Pseudo-words (half short and half long) with simple and contextual dependent rules were used. The length effect reduction on the reading speed, after repeated exposure, was considered an indicator of orthographic representation development, as the length effect is strong when reading unknown words, but absent when reading familiar words. The results show that dyslexic children have difficulties in developing orthographic representations, not only with context sensitive graphemes, but also with simple graphemes. In contrast to the control children, in the dyslexic group differences between reading times for short and long stimuli remained without significant changes after six presentations. Besides, this happened with sensitive context rules and also with simple grapheme-phoneme conversion rules. On the other hand, response and articulation times were greatly affected by length in dyslexic children, indicating the use of serial reading. Results suggest that the problems related to storing orthographic representations could be caused by a learning deficit, independently of whether the word contained context-sensitive rules or not.